If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6x + 1) = 14x + -11 Reorder the terms: 5(1 + 6x) = 14x + -11 (1 * 5 + 6x * 5) = 14x + -11 (5 + 30x) = 14x + -11 Reorder the terms: 5 + 30x = -11 + 14x Solving 5 + 30x = -11 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 5 + 30x + -14x = -11 + 14x + -14x Combine like terms: 30x + -14x = 16x 5 + 16x = -11 + 14x + -14x Combine like terms: 14x + -14x = 0 5 + 16x = -11 + 0 5 + 16x = -11 Add '-5' to each side of the equation. 5 + -5 + 16x = -11 + -5 Combine like terms: 5 + -5 = 0 0 + 16x = -11 + -5 16x = -11 + -5 Combine like terms: -11 + -5 = -16 16x = -16 Divide each side by '16'. x = -1 Simplifying x = -1
| -17+5=33 | | -4x-6=5x-6 | | 187-3x=33x+15 | | q+14=8(q+t) | | 0.5x-6=8 | | 8x-4x+7=1 | | 9x-75=6x-12 | | 5(3p+2)-2(4p-3)= | | 3x-1=8x | | ax-2x=a+2 | | 6x^2=7y | | c+2/4=3 | | 20x+6y=y | | 5d+13=2d-5 | | -54=6p-30 | | X-5-.10x=12+.5x | | 2x+5x=7Y+2 | | (X+4)(5x-6)=0 | | kx^2+12+k=0 | | x+45=56 | | -r=-12 | | 2(6-x)=-2(4-x) | | 9(x-3)=2(2x+9) | | x^4+2x^3-3x^2-36x=0 | | 6*(4-x)+6x=24 | | 32-5x=20-3x | | x-1+12=7x-25 | | 4x-6=5x-6 | | x+0.833(x)=7791.56 | | 3x^3+x=4x^2 | | 3x-2(6x-3)=42 | | 53+2x=18-3x |